Development of an LC-MS/MS technique and its validation for the determination of infigratinib in human K2EDTA plasma; Pharmacokinetics in healthy rabbits - Kunala Anusha, Gummadi Sowjanya (Journal of Applied Pharmaceutical Science, 2024)
A precise and linear liquid chromatography tandem mass spectrometry technique was developed for the estimation of infigratinib in human K2EDTA plasma. Chromatographic isolation of infigratinib and dasatinib was attained on orosil, 3 μm, C18, 150 × 4.6 mm stationary phase with a 0.8 ml/minute movable phase flow rate. The method was rectilinear in a concentration range of 1–1,640 ng/ml. Validation showed an r2 = 0.9997 and an equation of y = 0.0015x − 0.0063. The average accuracies of back-assessed concentrations for all quality controls (QCs) were between 96.34 and 100.76. At medium QC, high-QC, and low-QC concentrations, infigratinib had 98.14%, 96.36%, and 97.21% mean recoveries, respectively. Retention time %CV findings were ≤0.62 for the analyte and dasatinib, respectively. The developed method was successfully applied to the pharmacokinetic studies of infigratinib in healthy rabbits. The Cmax, Tmax, and T1/2, of the infigratinib tablets were 87.25 } 1.43 ng/ml, 6.0 } 0.03 hours, and 15.24 } 0.53 hours, respectively. AUC 0–∞ infinity for infigratinib tablets was 291.74 } 3.67 ng h/ml. The developed method was successfully validated and can be utilized for the assessment of infigratinib in biological matrices at industries, forensic laboratories, QC laboratories, and bioavailability studies.
Keywords: Infigratinib, cancer, LCMSMS, validation, accuracy, kinetics in rabbits